Pengaruh "GEMPI" (Game Pencegah Pernikahan Dini) terhadap Pengetahuan dan Sikap Remaja tentang Risiko Pernikahan Dini - Pratiwi, Intan Gumilang; Fitri Hamidiyanti, Baiq Yuni; Widyana, Erni Dwi (Midwifery Care Journal, 2025)
Â Early marriage in West Nusa Tenggara was caused by a variety of complicated circumstances, such as love and parental or family pressure. The majority of youngsters get married before they are old enough and without approval from the religious affairs office or Kantor Urusan Agama (KUA), which leads to illicit marriages, also known as unregistered marriages. In 2020, the West Nusa Tenggara Provincial Ministry of Religion recorded 139 teenage marriages in West Lombok Regency.The aim of this research was to analyzed GEMPI for increase knowledge and attitude adolence about early marriage. The research used One Group Pretest-Postest design. The study was held from August to September 2023, carried out in the Narmada Health Center's operational space in West Lombok Regency, West Nusa Tenggara. The population in this study were adolescents in Kramajaya Village, the Working Area of the Narmada Health Center, total 124 adolescents, the research sample was 30 adolescents with purposive sampling. The result showed there was effect GEMPI for increasing knowledge and attitude in adolescents about early marriage (p-value = 0,001) <( Î± = 0,05). Conclucion on the study that GEMPI had positive impact on knowledge and attitude in early marriage